Compensation of strong thermal lensing in an LD side-pumped high-power Er:YSGG laser. (24th September 2015) - Wang, Jintao; Cheng, Tingqing; Wang, Li; Yang, Jingwei; Sun, Dunlu; Yin, Shaotang; Wu, Xianyou; Jiang, Haihe
Abstract: The thermal focal length of the Er:YSGG crystal was measured using the resonator stability condition in the LD side-pumped laser system, and thermal focal lengths under different average input optical powers were obtained. The grinding radius was calculated according to the measured thermal focal length, and the strong thermal lensing was compensated by grinding negative curvatures on the crystal ends with the calculated grinding radius. The average output power of 10.1 W at a repetition frequency of 20 Hz was achieved, corresponding to the slope efficiency of 6.5% and optical–optical efficiency of 5.5%. The average output power was increased by 2.58 times after compensating at 20 Hz. The maximum pulse energy 562 mJ was achieved after compensating at 16 Hz. The corresponding divergence angles were measured to be about θ x = 8.13 mrad, θ y = 7.42 mrad, and the energy instability was 1.13%.